Working with Visual Impairment in Nigeria: A Qualitative Look at Employment Status. (November 2013) - Wolffe, Karen E.; Ajuwon, Paul M.; Kelly, Stacy M.
Introduction: This study presents the perceptions of employed individuals with visual impairments living in one of the world's most populous developing nations, Nigeria. Methods: The researchers developed a questionnaire that assessed personal and professional experiences among a sample of 172 adults with visual impairments living and working in Nigeria. Qualitative analyses of all the participants' responses to open-ended questions on the questionnaire were performed; as well as an analysis of responses from a subset of the participants who engaged in face-to-face interviews. Results: Participants identified out-of-date or inaccessible equipment and materials, coupled with inadequate assistance, transportation issues and environmental barriers, poor remuneration, weak job status, discrimination, lack of funds or time, inaccessible housing, and limited training opportunities as work challenges. The majority felt that further education was the key to improving their work situations. Discussion: This study validated the findings of the quantitative study with which it was aligned, underscoring the importance of education and access to employment for people with visual impairments. The participants in this study conveyed their thoughts about what worked and what did not work for them in employment. They also shared their ideas about how parental support had enabled them to achieve employment, and stressed the importance of disability-specific skills such as using assistive technology, mobility techniques, and independent living skills. Implications for practitioners: Practitioners are reminded of the importance of working closely with families to help them help their children acquire skills and the belief that they can work. They also need to remember the critical need for their students and clients to master disability-specific skills.